2004
DOI: 10.1111/j.1365-2370.2004.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB1 genotyping in patients with juvenile idiopathic arthritis in Taiwan

Abstract: The object of this study was to investigate whether there is an association between HLA-DRB1 alleles and the development of juvenile idiopathic arthritis (JIA) in Taiwan. HLA-DRB1 alleles were studied in 60 patients with JIA and 200 healthy controls using polymerase chain reaction (PCR)/sequence-specific oligonucleotide probes (SSO). The frequency of HLA-DRB1*0405 in patients with JIA was found to be significantly higher than that in healthy controls [odds ratio (OR) 2.64, 95% confidence interval (CI) 1.01-6.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…When the results of other studies from western countries were taken into consideration, we believe that the difference in immunogenetic background of ethnic groups may account for the differences in disease expression among the present study population. Our opinion has been supported by a number of studies 35–38 . It has been reported that JIA was primarily associated with HLA DRB1*08 and * 11, DQA1*0103, * 04 and *05 , and DQB1*04 alleles overall in Caucasian patients.…”
Section: Discussionsupporting
confidence: 77%
“…When the results of other studies from western countries were taken into consideration, we believe that the difference in immunogenetic background of ethnic groups may account for the differences in disease expression among the present study population. Our opinion has been supported by a number of studies 35–38 . It has been reported that JIA was primarily associated with HLA DRB1*08 and * 11, DQA1*0103, * 04 and *05 , and DQB1*04 alleles overall in Caucasian patients.…”
Section: Discussionsupporting
confidence: 77%
“…Incidence varies on a geographical basis per 1000 children, from 0.04 in Taiwan, 0.07 in Poland, 0.7 in USA, and 1.0 in UK to 4.0 in Australia [1,2]. The International League of Associations for Rheumatology (ILAR) provides the current international diagnostic standard for identifying seven clinically homogeneous subtypes of JIA [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…20 Although there is debate about whether rheumatoid arthritis and polyarticular JIA could be similar clinical conditions, 21 HLA-DRB1*04:05 may contribute to the pathogenesis of chronic arthritis at different ages and in different ethnic groups. Further studies are required to determine the molecular mechanisms by which HLA-DRB1*04:05 contributes to pathogenesis.…”
Section: Discussionmentioning
confidence: 99%